2018
DOI: 10.1111/iju.13891
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic management of percutaneous renal procedure‐related bleeding: A single‐center experience

Abstract: Objectives To present the radiological and clinical results of transcatheter arterial embolization in patients with active bleeding after percutaneous renal procedures. Methods A total of 79 consecutive patients who underwent angiography for percutaneous renal procedure‐related bleeding were included in the present retrospective analysis. Patient characteristics, angiographic management and clinical outcomes were analyzed. Results On angiography, bleeding foci were observed in 81.0% of the patients (64/79), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
3
21
1
Order By: Relevance
“…In the present study, Choi et al . reported the radiological and clinical results of TAE including a super‐selective technique used in patients with active bleeding after the percutaneous renal procedure . Consistent with similar reports, they concluded that TAE is a safe and effective method of treating bleeding related to percutaneous renal procedures …”
supporting
confidence: 60%
See 4 more Smart Citations
“…In the present study, Choi et al . reported the radiological and clinical results of TAE including a super‐selective technique used in patients with active bleeding after the percutaneous renal procedure . Consistent with similar reports, they concluded that TAE is a safe and effective method of treating bleeding related to percutaneous renal procedures …”
supporting
confidence: 60%
“…Interestingly, although previous studies on this topic have reported similar conclusions, the sample size of the present study was relatively large compared with that of the other studies, which is the strength of this study . The current report also includes cases of iatrogenic renal bleeding as opposed to accidental renal injury; therefore, data were available before renal bleeding and after TAE, allowing the authors to evaluate the chronological changes in renal function . There was no statistical difference in the estimated glomerular filtration rate from before the renal procedure to 7 days after TAE with the super‐selective technique, although renal function decreased at 1 or 3 days after TAE in some cases, probably because of damage from the bleeding rather than the TAE itself.…”
mentioning
confidence: 49%
See 3 more Smart Citations